Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM69 - Ingo Grevemeyer (PANGAEA, 2025)
Raw multibeam bathymetry data were collected aboard RV MARIA S. MERIAN during cruise MSM69 using a Kongsberg 12kHz EM 122 multibeam echosounder with 2°x2° beam width. The expedition took place during 2017-11-14 – 2017-12-22 from Mindelo to Mindelo (Cape Verde) in the Central Atlantic. Data were recorded in the EEZ of Cape Verde and outside. MSM69 focused on two main topics: 1. studying the crustal accretion process of the Mid-Atlantic Ridge as a function of time, surveying periodicities of crustal/lithospheric formation at slow-spreading rates; and 2., revealing the structure of the uppermost lithospheric mantle, including the evolution of seismic velocity structure with age and detecting any layering and seismic properties of the mantle (including the base of the lithosphere). Sound velocity profiles (SVP) were applied on the data for calibration. Please see the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by GEOMAR Helmholtz Centre for Ocean Research, provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.